Pressure-Induced Charge-Order Melting and Reentrant Charge Carrier Localization in the Mixed-Valent Pb3Rh7O15 - 李妍 孙朝 蔡嘉伟 孙建平 王铂森 赵志颖 Y. Uwatoko 闫加强 程金光 (Chinese physics letters, 2017)
The mixed-valent Pb3Rh7O15 undergoes a Verwey-type transition at Tv≈180K, below which the development of Rh3＋3＋/Rh4＋4＋ charge order induces an abrupt conductor-to-insulator transition in resistivity. Here we investigate the effect of pressure on the Verwey-type transition of Pb3Rh7O15 by measuring its electrical resistivity under hydrostatic pressures up to 8GPa with a cubic anvil cell apparatus. We find that the application of high pressure can suppress the Verwey-type transition around 3GPa, above which a metallic state is realized at temperatures below ～70K, suggesting the melting of charge order by pressure. Interestingly, the low-temperature metallic region shrinks gradually upon further increasing pressure and disappears completely at P〉7GPa, which indicates that the charge carriers in Pb3Rh7O15 undergo a reentrant localization under higher pressures. We have constructed a temperature-pressure phase diagram for Pb3Rh7O15 and compared to that of Fe3O4, showing an archetype Verwey transition.